Experience in Developing a Courseware to Inculcate Awareness Towards Disaster Risk Reduction Among Schoolchildren - Thiruchelvam, Sivadass; Chit, Suwannit Chareen; Mustapha, Kamal Nasharuddin; Ghazali, Azrul (2018)
Rising concern over climate change has substantially affected our daily lives. After Hurricane Harvey, the focus on global flood disaster has shifted to Asian region as exceptionally deadlier rainfall has killed at least 1200 people in 2017. Malaysia constantly faces this calamity on annual basis which caused serious social and economic impacts. Within the context of vulnerability, children are severely exposed to physical and psychological effects. Therefore, it is imperative to educate schoolchildren on awareness for flood disaster safety and resilience. The advent of courseware in the domain of disaster management has been well received due to its capability to educate children on preparation and mitigation for any catastrophes. Grounding upon AGILE technology, a courseware entitled “Jom Siap Bersama Si Kelip” has been developed for educating schoolchildren living nearby to hydropower dams in Peninsular Malaysia. This courseware aims to educate schoolchildren on flood disaster and what to do in the event of a flood. It is foreseen that this courseware will build a sense of confidence and control in handling moments of crisis amongst the targeted schoolchildren should any occurrence of flood disaster in the future.